Pengaruh Project Based Learning terhadap Self-efficacy dan Kemampuan Berpikir Kreatif - Nurrohmah, Eka Nurrohmah; Jalmo, Tri Jalmo; Yolida, Berti Yolida (FKIP Universitas Lampung, 2017)
The Effect of Project Based Learning towards Self-efficacy and Creative Thinking Skills. This study aims were to determine the effect of project based learning toward self-efficacy and the significant effect of the project based learning toward creative thinking skills. The population of study were all students of grade VII of SMP Negeri 13 Bandar Lampung. The samples of study were students of grade VII.5 and VII.2 that were selected by cluster random sampling technique. The design of study was the pretest-posttest nonequivalent control group design. Data of self-efficacy and creative product were obtained by using the scale of self-efficacy and creative product assessment rubric which were analyzed descriptively while the data of creative thinking skills were obtained by using pretest and posttest scores were analyzed by the Independent Sample t-test at a significant level of 5%. The results showed that the project based learning had an effect toward self-efficacy with high criteria. The project based learning has a significant effect toward creative thinking skills and creative products with creative criteria.Keywords: creative thinking skills, project based learning, self-efficacy DOI: http://dx.doi.org/10.23960/jpmipa/v18i2.pp38-50